Dopamine effects on frontal cortical blood flow and motor inhibition in Parkinson's disease. (June 2019) - Trujillo, Paula; van Wouwe, Nelleke C.; Lin, Ya-Chen; Stark, Adam J.; Petersen, Kalen J.; Kang, Hakmook; Zald, David H.; Donahue, Manus J.; Claassen, Daniel O.
Abstract: Parkinson's disease (PD) is characterized by dysfunction in frontal cortical and striatal networks that regulate action control. We investigated the pharmacological effect of dopamine agonist replacement therapy on frontal cortical activity and motor inhibition. Using Arterial Spin Labeling MRI, we examined 26 PD patients in the off- and on-dopamine agonist medication states to assess the effect of dopamine agonists on frontal cortical regional cerebral blood flow. Motor inhibition was measured by the Simon task in both medication states. We applied the dual process activation suppression model to dissociate fast response impulses from motor inhibition of incorrect responses. General linear regression model analyses determined the medication effect on regional cerebral blood flow and motor inhibition, and the relationship between regional cerebral blood flow and motor inhibitory proficiency. We show that dopamine agonist administration increases frontal cerebral blood flow, particularly in the pre-supplementary motor area (pre-SMA) and the dorsolateral prefrontal cortex (DLPFC). Higher regional blood flow in the pre-SMA, DLPFC and motor cortex was associated with better inhibitory control, suggesting that treatments which improve frontal cortical activity could ameliorate motor inhibition deficiency in PD patients.